Perfluoroalkyl substances and blood pressure in exposed young population in the Veneto Region, Italy. (30th September 2020) - Canova, C; Jare Zeddi, M; Barbieri, G; Gion, M; Daprà, F; Russo, F; Fletcher, T; Pitter, G
Abstract: Background: Residents in a large area of the Veneto Region (North-Eastern Italy) were exposed to perfluoroalkyl substances (PFASs) via drinking water. Studies on the association between PFASs and blood pressure (BP) levels are limited and results are inconsistent. Using cross-sectional data from the Regional health surveillance program, we aimed to quantify the associations between PFAS serum concentrations and blood pressure and hypertension prevalence. Methods: The study included 16, 224 individuals aged 20-39 years. Pregnant women (n = 327), participants with self-reported diagnosis or under treatment (n = 296) or with missing information on the selected covariates (n = 114) were excluded, leaving 15, 487 subjects. Hypertension (HYP) was defined as any self-reported diagnosis, use of antihypertensive drugs, or raised systolic/diastolic blood pressure (SBP)≥140, DBP ≥90 mmHg). Serum PFASs were measured by HPLC-MS. Generalized additive models were used to investigate the relation between each PFAS (perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorohexane sulfonic acid (PFHxS), and perfluorononanoic acid (PFNA)) ln transformed and by decile, and SBP, DBP, HYP, adjusted for potential confounders. Results: Both SBP and DBP increased significantly with an increase in the ln-transformed serum PFASs concentration in a monotonic way. The predicted increase in SBP and DBP were 1.62 (95% CI = 0.69, 2.55), 1.64 mmHg (95% CI = 0.96, 2.31) from lowest to highest decile of PFOA. The associations were stronger for SBP in men and DBP in women. One unit increase in each ln-PFAS was positively associated with an increased odds of HYP in men: PFOA OR = 1.07 (1.01-1.14), PFOS OR = 1.18 (1.05-1.32), PFHxS OR = 1.11 (1.03-1.19), PFNA OR = 1.19 (1.01-1.41). Conclusions: Our findings suggest that exposure to PFAS is associated with increased blood pressure and thus may contribute as a risk factor for the development of cardiovascular diseases. Key messages: Serum PFASs were associated with raised systolic blood pressure in men and diastolic blood pressure in women in a large highly exposed young adult population. Serum PFASs were associated with raised prevalence of hypertension in men.